2014
DOI: 10.1371/journal.pone.0098741
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in Abundance of Oral Microbiota Associated with Oral Cancer

Abstract: Individual bacteria and shifts in the composition of the microbiome have been associated with human diseases including cancer. To investigate changes in the microbiome associated with oral cancers, we profiled cancers and anatomically matched contralateral normal tissue from the same patient by sequencing 16S rDNA hypervariable region amplicons. In cancer samples from both a discovery and a subsequent confirmation cohort, abundance of Firmicutes (especially Streptococcus) and Actinobacteria (especially Rothia)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
321
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(368 citation statements)
references
References 55 publications
(75 reference statements)
27
321
3
2
Order By: Relevance
“…Bacterial cell lysis, the first step in DNA extraction, could be accomplished by several methods on the basis of either enzymatic, chemical or mechanical protocols and a combination of these methods (Huang et al, 2011, Jiang et al, 2014, Niwa et al, 2005, Said et al, 2014, Schmidt et al, 2014. A number of workers have compared different commercial kits and non-commercial protocols using either human samples or a laboratory created bacterial community (Claassen et al, 2013, Kennedy et al, 2014, McOrist et al, 2002, Wagner Mackenzie et al, 2015, Yuan et al, 2012.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Bacterial cell lysis, the first step in DNA extraction, could be accomplished by several methods on the basis of either enzymatic, chemical or mechanical protocols and a combination of these methods (Huang et al, 2011, Jiang et al, 2014, Niwa et al, 2005, Said et al, 2014, Schmidt et al, 2014. A number of workers have compared different commercial kits and non-commercial protocols using either human samples or a laboratory created bacterial community (Claassen et al, 2013, Kennedy et al, 2014, McOrist et al, 2002, Wagner Mackenzie et al, 2015, Yuan et al, 2012.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Its open-ended character allows for the discovery of new taxa potentially related to disease, and its culture-independent nature does not exclude species and phylotypes that are difficult to grow or currently uncultivated but that might have a role in disease initiation. The most recent studies of the association between the oral microbiome and OSCC have used 454 pyrosequencing (Schmidt et al 2014;Guerrero-Preston et al 2016). However, this form of sequencing has recently been outperformed by MiSeq Illumina sequencing (Caporaso et al 2012), which has a lower error rate and generates over 10 times more reads (Nelson et al 2014) and has thus become the leading sequencing platform for human microbiome studies (Amarasekara et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Other predominant genera such as Rothia, Prevotella, Capnocytophaga and Neisseria, might be involved in the susceptibility of an individual to periodontal disease (Ling et al 2010). In contrast Schmidt et al (2014) reported that in the cancer tissue samples Firmicutes (especially Streptococcus) and Actinobacteria (especially Rothia) was significantly decreased relative to contralateral normal tissue samples from the same patient. In another study Devi and Singh (2014), reported that after standard radiotherapy, there was a profound shift in the oral microflora to predominance of acidogenic microbes, primarily Streptococcus mutans and Lactobacilli coincident with a decrease in salivary flora and an increase in caries risk.…”
Section: Changes In Oral Cavity Microflora After Radiotherapymentioning
confidence: 83%